Dielectric properties and spectral characteristics of photocatalytic constant of TiO2 nanoparticles doped with cobalt - Bessergenev, Valentin G. (2021)
Dielectric properties and spectral dependence of the photocatalytic constant of Co doped P25 Degussa powder were studied. Doping of TiO2 matrix with cobalt was achieved by precipitation method using of Tris(diethylditiocarbamate)Co(III) precursor (CoDtc–Co[(C2H5)2NCS2]3). Five different Co contents with nominal Co/Ti atomic ratios of 0.005, 0.01, 0.02, 0.05 and 0.10 were chosen. Along with TiO2:Co samples, a few samples of nanopowders prepared by Sol-Gel method were also studied. As it follows from XPS and NMR studies, there is a concentration limit (TiO2:0.1Co) where cobalt atoms can be uniformly distributed across the TiO2 matrix before metallic clusters start to form. It was also shown that CoTiO3 phases are formed during annealing at high emperatures. From the temperature dependence of the dielectric constant it can be concluded that the relaxation processes still take place even at temperatures below 400 ◦C and that oxygen defect Ti–O octahedron reorientation take place at higher temperatures. The spectral dependency of the photocatalytic constant reveals the presence of some electronic states inside the energy gap of TiO2 for all nanopowdered samples.